2018
DOI: 10.1128/jb.00215-18
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Regulated Intramembrane Proteolysis: Protease MucP Can Overcome Mutations in the AlgO Periplasmic Protease To Restore Alginate Production in Nonmucoid Revertants

Abstract: The progression of cystic fibrosis (CF) from an acute to a chronic disease is often associated with the conversion of the opportunistic pathogen from a nonmucoid form to a mucoid form in the lung. This conversion involves the constitutive synthesis of the exopolysaccharide alginate, whose production is under the control of the AlgT/U sigma factor. This factor is regulated posttranslationally by an extremely unstable process and has been commonly attributed to mutations in the () gene. By exploiting this unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
1
19
1
Order By: Relevance
“…It has been observed that mucoid strains frequently revert to nonmucoid by acquiring mutations in algT (19, 25, 38). To determine what other mutations we could identify in algT that result in nonmucoid reversion, we grew mucoid PDO300 under low aeration, a stressful condition that selects for reversion (19). We isolated 18 PDO300 nonmucoid revertants and then sequenced algT to determine what proportion had acquired mutations in this gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed that mucoid strains frequently revert to nonmucoid by acquiring mutations in algT (19, 25, 38). To determine what other mutations we could identify in algT that result in nonmucoid reversion, we grew mucoid PDO300 under low aeration, a stressful condition that selects for reversion (19). We isolated 18 PDO300 nonmucoid revertants and then sequenced algT to determine what proportion had acquired mutations in this gene.…”
Section: Resultsmentioning
confidence: 99%
“…We found that 3 out of the 6 PDO300 and PDO300 Δ algD suppressors contained mutations in the MucA protease, mucP. MucP is a zinc metalloprotease that participates in the proteolytic cascade that degrades MucA (18, 19, 42). Delgado et al analyzed the MucP sequence and found four possible transmembrane domains, one beta-loop domain, a metalloprotease zinc-binding motif, two PDZ binding domains, and a RIP motif (19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the abundance of PA14_01490 (PA0122/RahU), a Rhl activated lipid binding protein, was decreased with both lactonase treatments but to a greater extent with SsoPox W263I (fold change of −959 and −107 vs. control and GcL) (Miklavič et al, 2015). Conversely, GcL induced a stronger decrease of Tsp (or AlgO), a protein part of alginate synthesis regulation, than SsoPox W263I (fold change of −115 and −35 vs. control and SsoPox W263I) (Qiu et al, 2007;Hay et al, 2014;Delgado et al, 2018). However, AlgU, the alginate regulator, and OprF, a pleiotropic porin also involved in biofilm formation, were only significantly reduced with SsoPox W263I (Hay et al, 2014;Chevalier et al, 2017).…”
Section: Treatment Of Pa14 With Different Lactonases Leads To Distincmentioning
confidence: 98%